Post-endoscopic retrograde cholangiopancreatography cholangitis after endoscopic treatment of post-transplant biliary strictures: a retrospective study - Zhang-Hagenlocher, Christine; Koschny, Ronald; Rupp, Christian; Michl, Patrick; Mehrabi, Arianeb; Wehling, Cyrill; Kantowski, Marcus; Sauer, Peter (BMC surgery, 2025)
Background and aim Biliary strictures after liver transplantation are associated with significant morbidity and mortality. Endoscopic retrograde cholangiopancreatography (ERCP) is the preferred approach. Post-ERCP cholangitis is a complication of this procedure. We aimed to evaluate the incidence of post-ERCP cholangitis in patients with post-transplant biliary strictures, their impact on survival, and identify potential risk factors. Methods This retrospective study evaluated liver transplant recipients with biliary strictures treated with balloon dilatation at defined intervals. Primary clinical endpoints were the incidence of post-ERCP cholangitis, overall survival, and identification of potential risk factors. Results Two hundred patients with a median follow-up period of 6 years (IQR 2-10 years) were included. Anastomotic and non-anastomotic strictures were diagnosed in 132 and 68 patients, respectively. Overall, 930 ERCP procedures were performed, and post-ERCP cholangitis was detected in 148 procedures (15.9%). Patients with post-ERCP cholangitis showed significantly worse overall survival rates (median, 9 vs. 15 years; log-rank test, p < 0.001), were significantly more frequently diagnosed with non-anastomotic strictures (44.6% vs. 25%; p = 0.004), and had significantly higher treatment failure rates (n = 24/92; 26.1% vs. n = 13/108; 12%; p = 0.02) compared to those without cholangitis. Independent risk factors for cholangitis included the presence of non-anastomotic strictures (OR 3.1), and first-time ERCP intervention with sphincterotomy (OR 6.31). Conclusions Post-ERCP cholangitis is a relevant complication of endoscopic treatment and is associated with the presence of non-anastomotic strictures and higher treatment failure rates. Since the success rate of endoscopic intervention in these complex strictures is limited, an optimized peri-interventional management and tailored antibiotic therapy may become particularly important for the further treatment and prognosis of these patients.
Gesehen am 08.12.2025